Development Frameworks of the Indonesian Partnership 21st-Century Skills Standards for Prospective Science Teachers: A Delphi Study (Jurnal Pendidikan IPA Indonesia, 2019)
In the 21st century, students from all levels of education face extreme global competition, technology that is driven by information, and rapid media-saturation. These dramatic accelerational challenges are the reason why the educational system must prepare students with the skills needed in the era of globalization. Based on a document published by The Board of National Education Standards in 2010 on the importance of establishing a framework for 21st-century education in Indonesia, the necessity of appropriate standards has become very important to the current educational system. This paper aims to discuss conceptual frameworks for prospective science teachers in Indonesia. Using an extensive literature review of three document (P21, enGauge-21CS, and ATC21S) and group discussion with a two-round Delphi study, we have constructed the Indonesian Partnership for 21st-Century Skills Standards (IP-21CSS) based on an agreement between 15 panelists. From the results of this study, we have established four IP-21CSS that were perceived by panelists as appropriate standards for prospective science teachers in Indonesia ranging from 4.5 to 5 or in the high level. These standards include: (1) 4Cs (critical thinking, creative thinking, collaboration, and communication); (2) ICTs (technology, media, and information literacy); (3) spiritual values (religious beliefs and spiritual awareness); and (4) character building (teachers’ attitudes and scientific attitudes). Therefore, it concludes that the implementation of 21st-century education learning that emphasizes each IP-21CSS indicator needs to be considered as an essential component in the courses process for prospective science teachers in Indonesia.